2009
DOI: 10.1007/s10194-009-0174-7
|View full text |Cite
|
Sign up to set email alerts
|

The validity of questionnaire-based diagnoses: the third Nord-Trøndelag Health Study 2006–2008

Abstract: The Nord-Trøndelag Health Study (HUNT 3) performed in 2006–2008 is a replication of the cross-sectional survey from 1995 to 1997 (HUNT 2). The aim of the present study was to assess the sensitivity and specificity of questionnaire-based headache diagnoses using a personal interview by a neurologist as a gold standard. For the questionnaire-based status as headache sufferer, a sensitivity of 88%, a specificity of 86%, and a kappa statistic of 0.70 were found. Chronic headache, chronic tension-type headache (TTH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
177
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(185 citation statements)
references
References 10 publications
8
177
0
Order By: Relevance
“…The major strengths of this study were its population-based design, the large sample size, and the use of validated headache diagnoses with good sensitivity and high specificity for both migraine and TTH (20). In the multivariate analyses, we were able to adjust for potential confounding factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major strengths of this study were its population-based design, the large sample size, and the use of validated headache diagnoses with good sensitivity and high specificity for both migraine and TTH (20). In the multivariate analyses, we were able to adjust for potential confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals who answered "no" to the screening question were classified as "headache free" and regarded as the reference group. The validity of these questionnaire-based diagnoses has been reported previously (20): for any headache, Hagen et al found the sensitivity to be 88% and specificity 86% (kappa value 0.70, 95% CI 0.61-0.79); for migraine, the sensitivity was 51% and specificity 95% (kappa values 0.50, 95% CI 0.32-0.68); and for TTH ≥1 days/month the sensitivity was 96% and specificity was 69% (kappa value 0.44, 95% CI 0.30-0.58).…”
Section: Headache Diagnosismentioning
confidence: 99%
“…For frequent headache (headache >6 days per month), and CDH (headache >14 days per month), the kappa values were 0.50, and 0.44, respectively. The validity of the year 2010 criteria were reported recently (18). For the questionnaire-based status as headache sufferer, a sensitivity of 88%, a specificity of 86%, and a kappa value of 0.70 were found for the Q2 questionnaire of HUNT 3.…”
Section: Validity and Reliability Of The Headache Diagnosesmentioning
confidence: 96%
“…Therefore, a revised version of the IHS criteria called 'liberal' migraine (Table 1) were defined to estimate the 1-year prevalence (14). In the two validation studies, acceptable agreement was found between the questionnaire-based 'liberal' migraine diagnosis and the migraine diagnosis made by clinical interview (17,18). We have also assessed 'liberal' migraine in the second 'head-HUNT', and found a small, but significant (P < 0.001), increase from 12.1% to 13.2%.…”
Section: Migrainementioning
confidence: 99%
“…Current headache was defined according to the validated question from the local population based health study (HUNT): "Have you suffered from headaches during the last year?" 14,15 Acute headaches lasting less than a week before the diagnosis were excluded since pituitary apoplexy is a known cause of headache and could act as a confounder. 12,16,17 In six patients, a bleeding/apoplexy was seen on the initial MRI, making pituitary apoplexy the likely cause of the acute headache.…”
Section: Headache Assessmentmentioning
confidence: 99%